Strengthening and harmonizing food policy systems to achieve food security: A case study and lessons from Ghana - Babu, Suresh Chandra; Blom, Sylvia (International Food Policy Research Institute, 2017)
Understanding how various entities in a policy system at the national level can contribute to improved use of evidence in policy making. Yet little research has focused in developing countries on how various actors and players in a policy system work together to achieve a set of policy goals. In this paper, we study the factors contributing to the effectiveness of a policy system. The process of policy design, adoption, implementation, and refinement requires an effective policy system as well as a capacitated and supportive institutional structure. External actors both through technical and financial assistance often support policy systems in developing countries. Poor coordination and harmonization of such assistance among various actors and players within the country can often result in undermining the very policy systems they try to strengthen. This is typical in the African agricultural development process. In this paper, we develop a conceptual framework for understanding the policy and institutional architecture of food and agriculture policy system and for improving the coordination and harmonization of the roles of policy actors and players. Applying the framework to Ghana, we map and analyze the organizational contributions of various actors and their functional characteristics. We show how such analysis can aid various policy actors in setting priorities and strategies for increasing their capacity and the effectiveness of their roles. Finally, we draw lessons for strengthening the food policy systems in developing countries through effective coordination among local and external actors.